Membuka dan Menutup Layar Proyek Secara Otomatis Menggunakan Arduino Uno - Dian Iis Cahyani; Muzdalifah; Nasruddin (Scientific Literacy Innovation and Technology Journal, 2024)
The development of computer hardware technology that supports the globalization of informatics, especially in the Indonesian context which focuses more on computers and programming in Informatics Engineering. Projector screens, for example, are a major focus, and automation of opening and closing projector screens is recognized as having provided significant support for various agencies, including government offices, companies, and educational institutions. Several studies related to the application of Arduino technology in various contexts are also presented, including rice grain moisture monitoring systems, room security systems, automation of opening and closing clotheslines and house doors, as well as tools for opening and closing floodgates for rice fields. However, there is a mismatch in using a manual projector at the UUP Class III Belang-Belang Transportation Office, which prompted the author to develop an automation tool for opening and closing the projector screen using Arduino. This research uses data collection methods in the form of literature study, interviews, and observation. The results of hardware and software testing, as well as implementation at the research location, show good performance. Thus, this research contributes to the development of technology in the context of automating opening and closing of projector screens using Arduino, with the hope of providing convenience and efficiency in using projector screens in various environments. In research on the design of automation for opening and closing projector screen devices using Arduino, it can be concluded that the designed model successfully utilizes the Arduino microcontroller system, L298N DC motor shield, and infrared as access control